Sidewalking : coming to terms with Los Angeles - Ulin, David L. (Oakland, Calif. : University of California Press, 2015)
"[Presents] an impressionistic take on Los Angeles in its current moment, which is a flashpoint of great transition, as the city verticalizes and densifies. It is also a meditation on the history, natural and human, of a place that often is derided as having no sense of its own past"--Provided by publisher.
Street, haunting -- Los Angeles plays itself -- Falling down -- Sidewalking -- Mapping history -- Miracle Mile -- A walker, in the city.
Adult
Adult
Keywords: Streets -- California -- Los Angeles; Walking -- California -- Los Angeles; Streets -- Los Angeles (Calif.); Walking -- Los Angeles (Calif.); Los Angeles (Calif.) -- Description and travel; Los Angeles (Calif.) -- Description and travel